2001
DOI: 10.1002/ccd.1212
|View full text |Cite
|
Sign up to set email alerts
|

Excimer laser facilitated percutaneous coronary intervention of a nondilatable coronary stent

Abstract: A patient is described in which excimer laser percutaneous coronary intervention is performed inside a suboptimally expanded stent due to nondilatable calcified plaque. The use of excimer laser facilitated full expansion of the stent with a balloon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 23 publications
(30 reference statements)
0
16
0
Order By: Relevance
“…ELCA has been mainly used for debulking and modifying plaque before stenting in complex lesions; such as calcified lesions , thrombotic lesions , in‐stent restenosis , and chronic total occlusions . There have been reports describing management of plaque and calcification behind under‐expanded stents using ELCA . Egred performed ELCA inside an under‐expanded stent deployed in a severely calcified lesion to debulk and soften calcification behind the stent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ELCA has been mainly used for debulking and modifying plaque before stenting in complex lesions; such as calcified lesions , thrombotic lesions , in‐stent restenosis , and chronic total occlusions . There have been reports describing management of plaque and calcification behind under‐expanded stents using ELCA . Egred performed ELCA inside an under‐expanded stent deployed in a severely calcified lesion to debulk and soften calcification behind the stent.…”
Section: Discussionmentioning
confidence: 99%
“…The absorption of laser energy by blood and contrast medium leads to fast vapor bubble expansion and implosion, causing explosive dilation and invagination of adjacent vessel wall . Although the use of continuous saline flush is recommended to reduce excessive vessel injury , there have been some reports of the use of ELCA with contrast injection . Lam et al performed ELCA with concomitant contrast injection during lasing instead of continuous saline flush to manage a newly deployed, under‐expanded stent .…”
Section: Discussionmentioning
confidence: 99%
“…There was no complication. Management of refractory stent under‐expansion by laser angioplasty has been reported for a newly deployed stent as a staged procedure or in the context of in‐stent restenosis .…”
Section: Discussionmentioning
confidence: 99%
“…34,35 While having no impact on the calcification itself, ELCA modifies the plaque behind the stent, which weakens the overall resistance, thus enabling subsequent complete stent expansion. [36][37][38] We have found that delivering high power laser energy (80 mJ/mm 2 / 80 Hz), using the 0.9-mm X80 catheter in the absence of saline, or with contrast injection, amplifies the ablative effect. Within a stented environment 'contrast-mileu' lasing appears to be safe, facilitating high-pressure balloon stent expansion.…”
Section: Excimer Laser Coronary Atherectomy In Underexpanded Stents (Seementioning
confidence: 99%
“…Within a stented environment 'contrast-mileu' lasing appears to be safe, facilitating high-pressure balloon stent expansion. [36][37][38][39] This technique has been evaluated in the ELLEMENT registry of 28 patients. 40 Procedural success was achieved in 96.4 % (27/28) of cases, using an increase of either 1 cm 2 on intravenous ultrasound (IVUS) or 10 % using quantitative coronary angiography derived minimal stent diameter as a definition.…”
Section: Excimer Laser Coronary Atherectomy In Underexpanded Stents (Seementioning
confidence: 99%